Why Is Hyperparathyroidism Underdiagnosed and Undertreated in Older Adults?. (December 2018) - Dombrowsky, Alex; Borg, Benjamin; Xie, Rongbing; Kirklin, James K; Chen, Herbert; Balentine, Courtney J
Introduction: Hyperparathyroidism significantly decreases quality of life, yet elderly patients are underdiagnosed and undertreated even though parathyroidectomy offers definitive cure with minimal morbidity. The purpose of this study is to determine why older patients with hyperparathyroidism are not appropriately diagnosed and referred for parathyroidectomy. Methods: We reviewed charts for a random sample of 25 patients aged 75 and older who had hyperparathyroidism and were referred for surgical evaluation, and 25 who were not referred. Two reviewers independently evaluated medical records to identify reasons for delayed diagnosis of hyperparathyroidism and reasons for nonreferral for parathyroidectomy. Results: The median age of our cohort was 84 (80-96) years, 90% were women, 60% were white, and median follow-up was 5.5 (1-17) years. In 58% of all patients, an elevated serum calcium was not acknowledged. Even when calcium and parathyroid hormone levels were both elevated, the diagnosis was missed in 28% of patients, and 16% with clear symptoms of hyperparathyroidism remained undiagnosed. For 42% of patients, a nonsurgeon informed them that surgery offered no benefit. Surgery was also rejected as a treatment for 36% of patients despite the development of new symptoms or rising calcium. Conclusions: Substantial gaps exist in processes for diagnosis and referral of patients with hyperparathyroidism that lead to underdiagnosis and undertreatment. To improve rates of diagnosis and treatment, strategies are needed to educate nonsurgeons and patients about the benefits of surgery and to modify care processes to more efficiently diagnose and refer patients.